Being fast or cautious? Sociocultural conditions influencing the sexual pathways of Black females in the United States - Natasha Crooks; Barbara King; Audrey Tluczek (BMC, 2022)
Abstract Background Black females in the United States face unique sociocultural conditions that impact their sexual development and increase their risk for sexually transmitted infections (STI), including but not limited to chlamydia, gonorrhea, and HIV. Research has not adequately explained how sociocultural conditions contribute to this increased risk. The purpose of our investigation was to explore the sociocultural conditions that influence Black cisgender females risk for STI. Methods This grounded theory study involved in-depth audio-recorded interviews with 20, primarily heterosexual, Black females ages 19-62. Results Findings informed a conceptual model that builds on previous theory about the sexual development of Black females and explains how sociocultural conditions impact two, participant identified, sexual pathways: Fast and Cautious. Movement on these sexual pathways was not always a linear trajectory; some participants shifted between pathways as their sociocultural contexts changed (i.e., sexual assault, STI, and level of protection). The Fast sexual pathway often led to greater STI risk. Conclusions This model may inform future research designed to prevent STI/HIV and promote the sexual health of Black females across the life course.